Preclinical sex differences in depression and antidepressant response: Implications for clinical research - Kokras, N; Dalla, C (J Neurosci Res, 2017)
Women suffer from depression and anxiety disorders more often than men, and as a result they receive antidepressants to a greater extent. Sex differences in antidepressant response in humans have been modestly studied, and results have been controversial. At the same time, preclinical studies on animal models of depression and antidepressant response have provided insights with regard to sex differences that could be useful for the design and interpretation of future clinical trials. This Mini-Review discusses such sex-differentiated findings with regard to the presentation of depression, endophenotypes, and antidepressant response. In particular, men and women differ in symptomatology of depression, and animal models of depression have revealed sex differences in behavioral indices. However, although in experimental studies behavioral indices and models are adjusted to identify sex differences properly, this is not the case in the use of depression rating scales in clinical studies. Accordingly, preclinical studies highlight the importance of sex differences at the baseline behavioral response and the underlying mechanisms that often converge after antidepressant treatment. This is also a neglected issue in human studies. Finally, preclinical research suggests that, in the quest for potential biomarkers for depression, sex should be an important factor to consider. Careful consideration of sex differences in preclinical research could facilitate and ameliorate the design and quality of clinical studies for disease biomarkers and novel fast-acting antidepressants that are so essential for both men and women suffering from depression. © 2016 Wiley Periodicals, Inc.
Keywords: *Drug Evaluation, Preclinical; animal models; Animals; Antidepressive Agents/*therapeutic use; Biological Markers; clinical trials; Depression/*drug therapy; Female; Gender; Humans; rating scales